2012
DOI: 10.1111/j.1749-4486.2012.02442.x
|View full text |Cite
|
Sign up to set email alerts
|

Amount of airflow required for olfactory perception in laryngectomees: a prospective interventional study

Abstract: The number of odours identified by laryngectomised patients increased with the volume of nasal airflow. The number of patients with rehabilitated olfactory function approximated the percentage of normosmic individuals in the non-laryngectomised population. These findings confirm the hypothesis that sense of smell is rehabilitated once the nasal airflow is re-established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
0
12
0
2
Order By: Relevance
“…One branch of clinical research that has confirmed the association between olfactory function and nasal airflow has been in the area of restoration of olfactory function in laryngectomy patients using the polite yawning technique . Manestar et al demonstrated that the minimum total nasal airflow required for olfactory stimulation in successfully rehabilitated patients was approximately 60 cm/second. However, determining how much of that total nasal airflow is directed to the olfactory region is complicated by several factors.…”
mentioning
confidence: 99%
“…One branch of clinical research that has confirmed the association between olfactory function and nasal airflow has been in the area of restoration of olfactory function in laryngectomy patients using the polite yawning technique . Manestar et al demonstrated that the minimum total nasal airflow required for olfactory stimulation in successfully rehabilitated patients was approximately 60 cm/second. However, determining how much of that total nasal airflow is directed to the olfactory region is complicated by several factors.…”
mentioning
confidence: 99%
“…The majority of studies referrers as the main cause for olfaction disorder in this population the total separation of the upper and lower airways causing the transference of the nasal air flow to a permanent tracheostomy tube, which makes it difficult for the air to get to the nasal cavity, where the olfactory epitheliumis [5][6][7] .…”
Section: Discussionmentioning
confidence: 99%
“…The interruption of the nasal airflow due to total laryngectomy hinders the odor molecules of reaching the olfactory epithelium and stops its stimulation, resulting in olfaction disorders [5][6][7] . Therefore, the total laryngectomized patient has a decrease in the olfactory perception (hiposmia) or even a total absence of olfaction (anosmia) 8,9 .…”
Section: Conflict Of Interest: Non-existentmentioning
confidence: 99%
“…Der Test ist sechs Monate haltbar und kann in dieser Zeit beliebig oft eingesetzt werden. Angewandt wurde er bisher zur Objektivierung von Geruchsstörungen vor und nach Laryngektomien sowie operativen Eingriffen im nasalen Bereich [75,76]. Erhältlich ist er bei der Firma Novimed Medizintechnik (Dietikon, Schweiz; www.smelldiskettes.com).…”
Section: Smell Diskettes Olfaction Testunclassified